Henry Heckelbeck spy vs. spy - Coven, Wanda (Coven, Wanda. Henry Heckelbeck, 2021)
"It's a spy versus spy world when Henry enters into a spying contest with one of his best friends, Max Maplethorpe. But will Max find out a little too much about Henry and his magical secret?"--